2020
DOI: 10.1080/03007995.2020.1762554
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of rivaroxaban versus warfarin in obese nonvalvular atrial fibrillation patients: analysis of electronic health record data

Abstract: Background: Although rivaroxaban has demonstrated consistent drug levels in normal weight and obese patients, sufficient confirmation of equal clinical effectiveness and safety is currently lacking. Purpose: To evaluate the effectiveness and safety of rivaroxaban versus warfarin for prevention of stroke and systemic embolism (SSE) in obese nonvalvular atrial fibrillation (NVAF) patients. Methods: Using Optum de-identified Electronic Health Record (EHR) data from November 2011 to September 2018,we evaluated NVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 26 publications
1
39
1
1
Order By: Relevance
“…A post-hoc analysis of the ROCKET AF trial showed that both rivaroxaban and warfarin are effective in stroke prevention across various BMI subgroups with no significant difference among subgroups (interaction p ¼ .537) 36 . Subsequent observational studies, including the present study, further substantiated this evidence [17][18][19][20][21][22][23] 21 . However, these findings were evaluated over a relatively short follow-up period of $10 months, which may explain part of the differences with the current study when evaluating patients with morbid obesity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A post-hoc analysis of the ROCKET AF trial showed that both rivaroxaban and warfarin are effective in stroke prevention across various BMI subgroups with no significant difference among subgroups (interaction p ¼ .537) 36 . Subsequent observational studies, including the present study, further substantiated this evidence [17][18][19][20][21][22][23] 21 . However, these findings were evaluated over a relatively short follow-up period of $10 months, which may explain part of the differences with the current study when evaluating patients with morbid obesity.…”
Section: Discussionsupporting
confidence: 79%
“…However, since this advisement, growing evidence in support of the safety and efficacy of DOACs in obese patients has emerged. In particular, emerging evidence suggests that DOACs are associated with a similar or lower risk of stroke/SE or major bleeding relative to the vitamin K antagonist warfarin in morbidly obese [17][18][19][20][21][22] and obese 23 patients with AF. However, much of this evidence is based on pooled data from patients who initiated different DOACs 17,18,20 , despite evidence that not all DOACs have the same pharmacokinetic profile in obese patients 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 These findings were consistent with those published by Costa el al on the effectiveness and safety of rivaroxaban for AF in obese patients across all BMI classes. 24 However, > 100 kg is commonly used to define high body weight with most of the patients falling between 100 kg and 120 kg. 25 For patients with BMI > 40 kg/m 2 , Kushnir et al recently demonstrated in a retrospective study including 795 patients receiving apixaban, rivaroxaban, or VKA for AF or VTE, similar efficacy and safety between FXa inhibitors and VKA.…”
Section: Thrombosis and Haemostasismentioning
confidence: 99%
“…As a class, DOACs seem to maintain their efficacy and safety for the treatment of VTE in patients with obesity, with similar data in the setting of NVAF. 94,95 Individually, the extent of data supporting each agent varies. Dabigatran demonstrates a reduced PK/PD profile in patients with obesity.…”
Section: Obesitymentioning
confidence: 99%